Effect of Cr3+ Doping on Magnetic Properties of Zn-Mg Ferrite Nanoparticles - Xiaogang Yu; Renpeng Yang; Chengwei Wu; Bo Liu; Wei Zhang (Magnetochemistry, 2023)
Zn0.6Mg0.4CrxFe2−xO4 (0 ≤ x ≤ 0.4) nanoparticles were synthesized using a hydrothermal technique. The obtained magnetic nanoparticles (MNPs) exhibited a spinel structure, where the lattice constant decreased with the Cr3+ ion content. The doping of Cr3+ ion (x = 0.1) increased the specific saturation magnetization to 46.4 emu/g but decreased to 20.0 emu/g with the further increase in the Cr3+ ion content to x = 0.4. The decrement in Curie temperature was ascribed to the weakened super-exchange interaction between the metal ions located at A-sites and B-sites, which arose from the doping of the Cr3+ ion. The T2-weighted images gradually darkened with the increase in Zn0.6Mg0.4Cr0.1Fe1.9O4 nanoparticles concentration, suggesting that the nanoparticles can enhance the image contrast. Zn0.6Mg0.4CrxFe2−xO4 (0 ≤ x ≤ 0.4) nanoparticles were able to heat the agar phantom to the hyperthermia temperature under the safe alternating magnetic field, which showed their potential in the magnetic induction hyperthermia.